2022
DOI: 10.2337/dc21-2064
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Impaired Olfactory Neural Activation and Cognitive Capacity by Liraglutide, but Not Dapagliflozin or Acarbose, in Patients With Type 2 Diabetes: A 16-Week Randomized Parallel Comparative Study

Abstract: OBJECTIVE The comparative neuroprotective effects of different antidiabetes drugs have not been characterized in randomized controlled trials. Here, we investigated the therapeutic effects of liraglutide, dapagliflozin, or acarbose treatment on brain functional alterations and cognitive changes in patients with type 2 diabetes. RESEARCH DESIGN AND METHODS Thirty-six patients with type 2 diabetes inadequately controlled with m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…By reviewing existing clinical trial and/or MR studies of medication treatment and/or drug repurposing on Alzheimer’s disease, we found that cholinesterase inhibitors and NMDA receptor antagonist were the two most widely used anti-dementia medications 42,43 , which were recommended by the current National Institute for Health and Care Excellence (NICE) guidance for people with Alzheimer’s disease (https://www.nice.org.uk/guidance/cg42). We also found some evidence to support the role of liraglutide (one GLP-1 inhibitor) and most of the anti-hypertensive drugs on preventing/delaying cognitive impairment 37,38,39,40,41 . The level of prevention of liraglutide was similar to the effect estimate we observed on metformin targets (14%) 37 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…By reviewing existing clinical trial and/or MR studies of medication treatment and/or drug repurposing on Alzheimer’s disease, we found that cholinesterase inhibitors and NMDA receptor antagonist were the two most widely used anti-dementia medications 42,43 , which were recommended by the current National Institute for Health and Care Excellence (NICE) guidance for people with Alzheimer’s disease (https://www.nice.org.uk/guidance/cg42). We also found some evidence to support the role of liraglutide (one GLP-1 inhibitor) and most of the anti-hypertensive drugs on preventing/delaying cognitive impairment 37,38,39,40,41 . The level of prevention of liraglutide was similar to the effect estimate we observed on metformin targets (14%) 37 .…”
Section: Discussionsupporting
confidence: 53%
“…By reviewing existing clinical trial and/or MR studies of drug repurposing on Alzheimer's disease, we found some evidence to support the role of liraglutide (one GLP-1 inhibitor) and most of the anti-hypertensive drugs on preventing/delaying cognitive impairment 37,38,39,40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…By reviewing existing clinical trial and/or MR studies of medication treatment and/or drug repurposing for Alzheimer's disease (from inception to 1 March 2021), we found some evidence to support the role of liraglutide (a GLP-1 inhibitor) and most of the antihypertensive drugs on preventing/ delaying cognitive impairment [37][38][39][40][41]. The level of prevention of dulaglutide (another GLP-1 inhibitor) was similar to the effect estimate we observed on metformin targets (14%) [37].…”
Section: Discussionmentioning
confidence: 99%
“…During the functional MRI scan, the individuals were asked to lie quietly with their eyes closed but not to fall asleep, not to think of anything in particular, and to avoid head movement. Structural images and functional images were obtained axially using the parameters described in our previous articles 16 . Additionally, fluid‐attenuated inversion recovery (FLAIR) scans were acquired with the following settings: repetition time/echo time (TR/TE) = 7000/120; slices = 18; thickness = 6 mm; gap = 1.3 mm; flip angle = 110°; and voxel size = 0.65 × 0.95 × 6 mm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Statistical Parametric Mapping (SPM12, Wellcome Trust Centre for Human Neuroimaging) and Data Processing and Analysis for Brain Imaging (DPABI_V4.2_190919, https://rfmri.org/dpabi) were used to preprocess fMRI data. Statistical Parametric Mapping preprocessing was undertaken in seven distinct steps in accordance with our previous study 16 . Anatomical images were processed using FreeSurfer, version 5.3 (http://surfer.nmr.mgh.harvard.edu/) with thorough manual editing to obtain cortical parcellations according to the Desikan‐Killiany Atlas.…”
Section: Methodsmentioning
confidence: 99%